تطبيق نموذج الانحدار الذاتي غير الخطي للشبكات العصبونية للتنبؤ بعكارة مياه الشرب في محطة تنقية السن - عوض عادل; جعفر رائد; عسيكريه عزيز (Latakia University Journal -Engineering Sciences Series, 2018)
Drinking water turbidity measuring is significant indicator of water quality, and represents a primary test to evaluate the stability of drinking water purification plant. Artificial neural networks (ANN) provide efficient tool to deal with the complex, dynamic and non-linear nature of purification processes. They have the ability to response to various instant changes in parameters influencing water purification. In this research a feed-forward back-propagation non-linear autoregressive neural networks with exogenous variables (NARX) were tested to predict the effluent turbidity from Al-Sin drinking water purification plant, which considered as a case study. The models were built based on daily turbidity, pH and conductivity of raw water data as well as daily rainfall over the reservoir while the daily effluent turbidity data were used for verify the performance accuracy of each network. The results of this research confirm that NARX models offers good results in modeling and simulating the non-linearity behavior of water turbidity as well as to predict its values. These models can be used in a permanently evaluation of the performance of Al-Sin drinking water purification in order to achieve the stabilization and supply a significant sector of the Syrian coast with drinking water. يعدّ قياس عكارة مياه الشرب مؤشراً هاماً على جودة المياه، ويمثل اختباراً أساسياً لتقييم استقرار عمل محطة تنقية مياه الشرب. توفّر الشبكات العصبونية الصنعية أداةً فعالة للتعامل مع الطبيعة المعقدة، والديناميكية، وغير الخطية لعمليات التنقية، ولديها القدرة على الاستجابة للتغيرات الآنية المختلفة للبارامترات المؤثرة في تنقية المياه. تم في هذا البحث اختبار شبكات الانحدار الذاتي غير الخطي مع متغيرات خارجية Non-Linear Autoregressive Neural Networks with Exogenous Variables (NARX)، وذات التغذية الأمامية، والانتشار العكسي للخطأ للتنبؤ بعكارة المياه الخارجة من محطة تنقية مياه الشرب في السن التي اعتُمدت كحالة دراسة. بُنيت النماذج بالاعتماد على بيانات عكارة، وناقلية، وpH مياه بحيرة السن الخام الداخلة إلى المحطة بالإضافة إلى بيانات الهطول المطري فوق حوض التغذية، واستخدمت بيانات عكارة المياه الخارجة من المحطة المقاسة يومياً للتحقق من دقة أداء الشبكة العصبونية الصنعية. أثبتت نتائج الدراسة أن النموذج المستخدم يُعطي نتائج جيدة في نمذجة ومحاكاة السلوك غير الخطي للعكارة، والتنبؤ بقيمها، ويمكن استخدامه في التقييم المستمر لأداء محطة تنقية مياه الشرب في السن بما يحقق استقراراً في عملها، وفي تزويد قطاع كبير من الساحل السوري بمياه الشرب.